MODERNISME DAN POSMODERNISME DALAM DESAIN: SEBUAH PENGANTAR TEORETIS - Aditya Ali (Universitas Informatika dan Bisnis Indonesia, 2018)
Modern is a term that has much to do with the advent of the early twentieth century. The most fundamental features are always associated with the concept of industrial revolution. The invention of Guttenberg printing press has always been the claim of the world of communication and design over the era of modernism. In its development, each field then performs new claims to modernism through a variety of products that only appear visually, visually, or functionally. The world of art, design, and architecture became a loyal manufacturer of modernism. But apparently, the concept of modernism also met the point of saturation. New concepts emerge by adopting a term that seems to negate modernism, namely postmodernism. In perkembangnnya, this term is not just a concept, but transformed into a movement and considered to be a threat to modernism, because it has a style of interest in the field of art, design, and architecture. This article provides an early paradigm of modernism and postmodernism especially in the field of design in theoretical framework based on the views of some related experts. Keywords: modernism, postmodernism, art and design.